CHARACTERISTICS OF PATIENTS WITH URINARY TRACT STONES AND PROFILE OF URIC ACID AND CHOLESTEROL AT KUSTATI ISLAMIC GENERAL HOSPITAL SURAKARTA IN THE PERIOD OF OCTOBER 2020 TO MARCH 2022 - Muhamad, Prasojo; Utomo, Ahmad Bi; Achmad, Tri Hanggono (Indonesian Urological Association, 2023)
Objective: This study aims to research the characteristic of patients with urinary tract stones and the profiles of uric acid and cholesterol at the Kustati Islamic General Hospital (RSUI) in the period from October 2020 to March 2022. Material & Methods: This research uses the cross-sectional retrospective approach with the descriptive method. The research subjects are the patients with urinary tract stones that have undergone operations in Kustati Islamic General Hospital in the period between October 2020 and March 2022 as well as patients that have had their level of uric acid and cholesterol examined in the laboratory of Kustati Islamic General Hospital in the period from October 2020 to March 2022. Results: Urinary tract stones occur the most in men (70.3%) and in the age group 46-59 years old with a percentage nearing 50%. Urinary tract stones occur the most in the upper section of the urinary tract, mainly in the kidneys (67.2%). Hyperuricemia occur mostly in men while hypercholesterolemia occur mostly in women. Conclusion: The location of stone is mostly found in the kidneys. Patients with hyperuricemia are mostly men, while patients with hypercholesterolemia are mostly women.